2019
DOI: 10.1186/s12883-019-1558-1
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic stroke in Morocco: a systematic review

Abstract: BackgroundThe aim of this systematic review is to determine the epidemiological and etiological profiles, the influential factors of the prehospital delay, thrombolysis management, the acute and 3-month mortality rate and the genetic aspect of ischemic stroke in Morocco.MethodsThe present work is a systematic review that was conducted according to the recommendations of the “Preferred reporting items for systematic reviews and meta-analysis”. We used Pubmed, Sciencedirect, Scopus, Clinicalkey, and Google schol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 55 publications
1
9
0
Order By: Relevance
“…This lack of knowledge of the warning signs of stroke potentially impacts on the early use of specialized hospital centers for possible management of stroke patients. This finding was missed in a recent Moroccan systematic review study [6]. To address this concern, the High Authority of Health in France recommended that the treating physician inform patients at risk (vascular history, high blood pressure, diabetes, arteriopathy of the lower limbs, and so on), as well as their entourage, about the main signs of stroke to contribute to rapid access to neurovascular units [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This lack of knowledge of the warning signs of stroke potentially impacts on the early use of specialized hospital centers for possible management of stroke patients. This finding was missed in a recent Moroccan systematic review study [6]. To address this concern, the High Authority of Health in France recommended that the treating physician inform patients at risk (vascular history, high blood pressure, diabetes, arteriopathy of the lower limbs, and so on), as well as their entourage, about the main signs of stroke to contribute to rapid access to neurovascular units [27].…”
Section: Discussionmentioning
confidence: 99%
“…Stroke incidence and mortality have increased in the countries of the Middle East and North Africa over the past decade, and projections indicate that stroke-related deaths will approximately double by 2030 in the same region [3,4]. Despite the rapid evolution of the generalization of intravenous thrombolysis in recent years in the countries of the Middle East and North Africa [5], the average symptom onset to arrival at a stroke center or emergency department (onset-to-door time [ODT]) of patients with ischemic stroke in Morocco remains very long, possibly resulting from a lack of knowledge, particularly of the first warning signs of an ischemic stroke, according to a recent systematic review [6].…”
Section: Introductionmentioning
confidence: 99%
“…The high performance of Morocco, on the other hand, was not mirrored in prior, yet limited literature. These studies have shown that while Morocco is already undergoing the epidemiological transition, the awareness of ischemic heart disease and CVD risk remained low in the population [52][53][54]. Hence, future research may yield valuable insights into the strengths and weaknesses of the Moroccan NCD care system.…”
Section: Plos Medicinementioning
confidence: 99%
“…It was reported that men in the Arab world were most often victims of stroke (between 55.9% and 75%). 8 In the NEMC-PCR, the patients of PCCI comprised 256 men (63%) and 151 women (37%). 4 Two previous studies on bilateral cerebellar infarction showed that 85% and 64% of the patients were male, respectively.…”
Section: Discussionmentioning
confidence: 99%
“… 11 The reason of the large proportion of male patients may be hormonal factors including estrogen, which seems to have protective effects on both the vascular and cerebral systems. 8 …”
Section: Discussionmentioning
confidence: 99%